2020
DOI: 10.3390/ph13120463
|View full text |Cite
|
Sign up to set email alerts
|

Non-Steroidal Anti-Inflammatory Drugs Increase Cisplatin, Paclitaxel, and Doxorubicin Efficacy against Human Cervix Cancer Cells

Abstract: This study shows that the non-steroidal anti-inflammatory drug (NSAID) celecoxib and its non-cyclooxygenase-2 (COX2) analogue dimethylcelecoxib (DMC) exert a potent inhibitory effect on the growth of human cervix HeLa multi-cellular tumor spheroids (MCTS) when added either at the beginning (“preventive protocol”; IC50 = 1 ± 0.3 nM for celecoxib and 10 ± 2 nM for DMC) or after spheroid formation (“curative protocol”; IC50 = 7.5 ± 2 µM for celecoxib and 32 ± 10 µM for DMC). These NSAID IC50 values were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 102 publications
2
24
0
Order By: Relevance
“…438,439 Furthermore, celecoxib, a specific COX2 inhibitor, increase the anti-tumor efficacy of cisplatin in cervix cancer cells, as well as in bladder cancer and gastric cancer. [440][441][442] Paclitaxel induces apoptosis by stabilizing microtubules, thereby leading to cell arrest. 442,443 In response to paclitaxel administration, a variety of inflammatory factors and signaling pathways, such as IL-1β, IL-8, IL-6, and NF-κB, can be activated.…”
Section: Therapy-elicited Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…438,439 Furthermore, celecoxib, a specific COX2 inhibitor, increase the anti-tumor efficacy of cisplatin in cervix cancer cells, as well as in bladder cancer and gastric cancer. [440][441][442] Paclitaxel induces apoptosis by stabilizing microtubules, thereby leading to cell arrest. 442,443 In response to paclitaxel administration, a variety of inflammatory factors and signaling pathways, such as IL-1β, IL-8, IL-6, and NF-κB, can be activated.…”
Section: Therapy-elicited Inflammationmentioning
confidence: 99%
“…[440][441][442] Paclitaxel induces apoptosis by stabilizing microtubules, thereby leading to cell arrest. 442,443 In response to paclitaxel administration, a variety of inflammatory factors and signaling pathways, such as IL-1β, IL-8, IL-6, and NF-κB, can be activated. [444][445][446][447] By using high doses of radiation to kill cancer cells and shrink tumors, radiotherapy is an important approach of cancer treatment.…”
Section: Therapy-elicited Inflammationmentioning
confidence: 99%
“…[30] More recent results showed that another copper(II)-hydrazone ligand derived from 4-methoxybenzohydrazide with o-vanillin displayed similar IC 50 values on breast cancer cells. [25] 2.9 � 0.5 82 � 4 [29] Many scientific evidences showed that copper drugs with IC 50 values lower than 10 μM can be consideredas powerful antitumor agents toward human cancer cell lines. [8] Taking into account the kind of ligand used in this work we found that Lu et al designed and synthetized different copper (II) complexes with vanillin Schiff base derivatives and naproxen with anticancer activity on bulk and breast cancer stem cells, with a moderate activity (37.6 � 3.3 and 36.0 � 4.6 μM respectively).…”
Section: Effect Of Cuhl On Cell Viability and Cell Proliferationmentioning
confidence: 99%
“…Therefore, PEG has been widely studied in the fields of controlled drug release, wound healing, and drug delivery [ 48 , 49 , 50 , 51 , 52 ]. Doxorubicin (Dox) is an anti-tumor drug that is clinically used for the treatment of acute myelogenous leukemia, acute lymphoblastic leukemia, Hodgkin’s and non-Hodgkin’s lymphoma, breast cancer, and other malignant tumors [ 53 , 54 , 55 , 56 , 57 , 58 ]. However, it displays a low utilization rate, causes severe adverse reactions, and an inability to effectively reach the sites of tumors [ 59 , 60 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%